Design of an Extrudate Filament Machine for Recycling Waste Polyethylene Terephthalate Plastics into 3D Printing Filament - AB RAHMAN, Putri Irda Ab Rahman; Mai Noor Asiah Tan Zalilah; Azlan Shah Katiman (Politeknik Aceh, 2024)
This research paper presents the design of an extrudate filament machine tailored for recycling waste Polyethylene Terephthalate (PET) plastics into filament suitable for 3D printing. The exponential growth of plastic waste, particularly PET, poses significant environmental challenges. Recycling PET into usable filament for 3D printers not only addresses environmental concerns but also promotes sustainable manufacturing practices. The design process encompasses a thorough analysis of requirements, considering factors such as input material variability, filament diameter consistency, and production throughput. Through conceptual and detailed design phases, the machine is optimized to effectively shred, melt, extrude, cool, and wind the recycled PET material into uniform filament spools. Material selection is carefully curated to ensure durability, thermal stability, and compatibility with PET recycling processes. The machine integrates various components such as shredders, extruders, cooling systems, and filament winding mechanisms to efficiently process waste PET plastics. Furthermore, the paper explores the economic feasibility and environmental benefits of implementing such a system for local plastic recycling initiatives.